"Artisan" as Brand: Adding Value In A Craft Chocolate Community. (2nd January 2017) - Leissle, Kristy
Abstract: Building upon the finding that the term "artisan" is a floating signifier in contemporary US chocolate marketing, this paper suggests that "artisan" functions similarly to brands for craft chocolate. This function is specific to the US post-Fordist creative economy and the rise of craft chocolate since 1997. Based on textual analysis of craft chocolate websites and packaging; comparisons between historical and contemporary uses of "artisan"; and results of a consumer survey on meanings of the term, this paper demonstrates that "artisan" has shifted away from denoting a labor class. Instead, it now suggests a community of producers and consumers who perceive shared priorities for this value chain. In this market reframing, "artisan" as a brand word has opened up new possibilities for value addition for chocolate.